El Excentrico, 1968-08-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
August 5, 1968 [5 de Agosto de 1968]. No Volume or issue number. Cover has a photo of newly married couple. The headline reads, "The Former Miss Anna Luisa Machado now Mrs. Roberto H, Cisneros."